Students’ Numeracy Skills in Solving Minimum Competency Assessment Questions on Geometry and Measurement Content - Azizah Azizah; Kartini Kartini; Yenita Roza (PRISMA, 2025)
The Minimum Competency Assessment (MCA) measures students’ numeracy skills, a crucial ability in the 21st-century digital era. However, PISA and the 2024 Indonesian Education Report show that Indonesian students’ numeracy skills remain low. This study aims to describe students’ numeracy skills in solving MCA questions on geometry and measurement content. The method used is descriptive with a qualitative approac. Data were collected through triangulation involving test results from seven MCA numeracy questions on geometry and measurement and through interviews. The subjects of this study consisted of 32 eighth-grade students from SMPN 40 Pekanbaru. The analysis of students’ answers revealed that 46.88% were categorized as low, 43.75% as moderate, and only 9.38% demonstrated a high level of numeracy proficiency. Interviews were conducted with selected students based on the results of the response analysis. Students in the high category were able to understand the context, interpret visual information, and apply reasoning and geometric concepts to real-life situations. They demonstrated the full range of cognitive processes, although improvements in accuracy are still needed. Students in the moderate category showed a lack of systematic thinking and often missed key details due to insufficient attentiveness when reading questions and selecting strategies. Meanwhile, students in the low category experienced fundamental difficulties in understanding visual information, units, and problem contexts. Their responses tended to be based on guesses rather than logical calculation, indicating the need for intensive support and more foundational instruction.